Vaccine hesitancy and refusal during the Covid-19 pandemic in Italy: Individualistic claims or repoliticization? - Lello, Elisa; Bertuzzi, Niccolò; Pedroni, Marco; Raffini, Luca (PARTECIPAZIONE E CONFLITTO, 2023)
The Covid-19 pandemic highlighted new (or renewed) forms of conflict within a longer path of distrust and dissatisfaction towards politics and growing scepticism towards 'official truths' and 'official science'. Italy was the first European and Western country in which the pandemic spread in February 2020, and also one that adopted particularly stringent measures to contain the virus. In this scenario, a country in which political distrust was particularly diffused experienced an increase in institutional trust, accompanied by a strong demand for security from above. At the same time, radicalisation and distrust have grown among larger strata of the Italian population, leading to a significant polarisation of the public sphere. This essay critically embraces the perspective of the vast and plural universe of vaccine hesitancy and refusal (VHR) and, more generally, the materialisations of conflict concerning vaccines and policies aimed to address the Covid-19 pandemic. In the media and public debate, these protests have been mainly regarded as populist, driven by individualistic claims nurtured by indifference towards the collective good. We specifically explore whether VHR should be viewed exclusively as a sign of selfishness and populism or also as a form of repoliticisation around new issues and, in particular, as an expression of critical citizenship manifesting doubts about the decisions made by politicians, affirming a critique of the model of instrumental rationality, and advocating a pluralist debate on complex issues which directly affect individual life-choices and the body. Our study is based on 67 qualitative interviews with VHR citizens and a focus group with four key figures of the 'Movimento 3V' (3VM), a minor Italian party advocating freedom of choice in relation to vaccines.